Dataset of confirmed Hospital for Tropical Diseases, HCMC Dengue patients - Kestelyn, E (University of Oxford, 2021)
Anonymised dataset of 4,131 adult and paediatric patients admitted to hospital in Ho Chi Minh City, Vietnam with a confirmed diagnosis of dengue.